Parafia szadkowska na początku XVI w. W świetle Liber beneficiorum Jana Łaskiego - Szkutnik, Piotr (Biuletyn Szadkowski, 2013)
The description of the parish of Szadek from 1521, included in Jan Laski’s Liber beneficiorum, is the oldest preserved complete register of the posessions and revenues of this parish. It contains toponomastic data on the property as Well as the legal and economic situation of Church at that time. It also provides information on the personnel and institutions connected With Church, such as hospitals and parish schools. The Latin edition of this description from 1880 is presented in this article. Its translation into Polish Was first published in 1817.